Differential properties in the ratings of certified versus non-certified bond-rating agencies - Beaver, William H.; Shakespeare, Catherine; Soliman, Mark T. (Journal of Accounting and Economics, 2006)
We examine whether the properties of bond ratings from certified agencies (designated by the Securities and Exchange Commission (SEC)) differ from those of non-certified bond-rating agencies. Bond ratings from non-certified agencies are used solely for investment advice. Certified ratings are used by a variety of constituents, many of whom write contracts incorporating these ratings. We find that the properties of the ratings from the two agency types differ in predictable ways. Our results show that the non-certified agency's ratings are consistent with their role of providing information to investors. The certified agency is generally more conservative, consistent with their significant role in contracting.